Does publication in top-tier journals affect reviewer behavior? - Aarssen, L; Lortie, C; Budden, A; Koricheva, J; Leimu, R; Tregenza, T (2009)
We show that when ecologists act as reviewers their reported rejection rates recommended for manuscripts increases with their publication frequency in high impact factor journals. Rejection rate however does not relate to reviewer age. These results indicate that the likelihood of getting a paper accepted for publication may depend upon factors in addition to scientific merit. Multiple reviewer selection for a given manuscript therefore should consider not only appropriate expertise, but also reviewers that have variable publication experience with a range of different journals to ensure balanced treatment. Interestingly since age did not relate to rejection rates, more senior scientists are not necessarily more jaded in reviewing practices.